2011
DOI: 10.3844/ajassp.2011.486.494
|View full text |Cite
|
Sign up to set email alerts
|

Application of Soil and Water Assessment Tools Model for Runoff Estimation

Abstract: Problem statement:The most of the distributed or physically-based hydrologic and water quality models from developed countries are not directly applicable in developing countries due to both lack of data and different climatic conditions. Hence, there is a need for a study to be conducted a catchment of developed countries. Approach: From a review of various models to estimate runoff using a semi-distributed model, Soil and Water Assessment Tool (SWAT) was selected. Sequential Uncertainty fitting (SUFI-2), a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…As a physically based hydrological model, SWAT requires a great deal of input data (Daggupati et al, 2011;Hosseini et al, 2011). Major input datasets include topography, soils, land use/land cover data and management practices, weather and hydrography.…”
Section: Swat Modelmentioning
confidence: 99%
“…As a physically based hydrological model, SWAT requires a great deal of input data (Daggupati et al, 2011;Hosseini et al, 2011). Major input datasets include topography, soils, land use/land cover data and management practices, weather and hydrography.…”
Section: Swat Modelmentioning
confidence: 99%
“…The uncertainty of input parameters in SUFI-2 is described as a uniform distribution, while model output uncertainty is quantified at the 95% prediction of uncertainty (95PPU) [43]. The 95PPU is calculated at the 2.5% and 97.5% levels of the cumulative distribution of an output variable obtained through Latin hypercube sampling, disallowing 5% of the very bad simulations [20].…”
Section: Sufi-2 Algorithmmentioning
confidence: 99%
“…are relatively more sensitive to runoff but less to sediment. Hosseini et al [10] applied the SWAT model for the runoff estimation in a Taleghan basin and found that the Baseflow alpha factors (ALPHA_BF) followed by Snowfall temperature (SFTMP) and Groundwater delay time (GW_DELAY) are more sensitive parameters.…”
Section: The Sensitivity Of Model Parametersmentioning
confidence: 99%
“…SUFI-2 combines calibration and uncertainty analysis to find parameter uncertainties while calculating the smallest possible prediction uncertainty range. Hence, these parameters uncertainty reflect all sources of uncertainty [10]. In SUFI-2, the uncertainty of input parameters is depicted as a uniform distribution, while model output uncertainty is quantified at the 95% prediction of uncertainty (95PPU).…”
Section: Introductionmentioning
confidence: 99%